Rekonstruksi Frasa Fasilitas Lainnya Dalam Tindak Pidana Korupsi Terkait Gratifikasi Seksual - Ade Irma Suryani; Ahmad Hasan Basri (Journal of Law and Islamic Law, 2023)
The Corruption Law requires adjustments to create legal certainty, therefore in this study the researcher will examine the reconstruction of the Elucidation of Article 12B Paragraph (1) in the Corruption Law. The reconstruction of this article is intended to create legal certainty regarding sexual gratification so that perpetrators of sexual gratification crimes can be punished. The research method used in this research is normative legal research. The approaches used in this study are statutory approaches, historical approaches, and conceptual approaches. The results of the study state that when the corruption crime regulations have not stated and regulated explicitly regarding sexual gratification, especially in the explanation of the phrase "other facilities", then based on a restrictive interpretation it is appropriate, namely by using a benchmark for providing facilities in the form of sexual services provided that they fulfill the elements of Article 12B, namely related to his position and/or contrary to his obligations or duties. This is also in line with the context of hermeneutics which emphasizes the intent of why the Corruption Law was issued. Women who are objects of sexual gratification can be charged with Article 15 of the Corruption Law in conjunction with Article 55 paragraph (1) of the Criminal Code because these women assist and participate in criminal acts of corruption and their criminal penalties are generally reduced by 1/3 (one third) of the criminal penalties. In Islamic Criminal Law, women who are objects of sexual gratification have committed adultery and the punishment for those who commit adultery is 100 floggings.